Epidemiology of Frequent/Urgent Urination in Older Adults in China: A Multicenter, Cross-Sectional Study - Zhang, Yiwen; Wang, Xiao-Dan; Song, Yehua; Peng, Ruiqiang; Tang, Ting; Li, Miaoduan; Yu, Zhenzhen; Ji, Yong; Niu, Jianping (Frontiers in Public Health, 2021)
Background: Frequent/ urgent urination is an event of multifactorial origin where ‎involuntary leakage of urine occurs. Epidemiological study of this condition is of high ‎importance due to its negative impact on psychological, physical, and social wellbeing ‎of the victims. Objective: This cross-sectional study was aimed to investigate the ‎prevalence of frequent/urgent urination in older adults in China. Method: In this study, ‎a face-to-face questionnaire survey was conducted between April 2019 to August 2019 ‎among 4,796 older adult populations in communities of Tianjin jizhou and Xiamen ‎jimei of China. Descriptive analysis, univariate regression and all statistics were ‎conducted in IBM SPSS v22. The count data were analyzed by χ2 Test. P < 0.05 was ‎considered statistically significant.‎ Results: In the total investigated population, the prevalence of frequent or urgent ‎urination was found in 1,164 patients (24.3%) with 31.7% (664 / 2,097) male patients ‎and 18.7% (500 / 2,699) female patients having male to female a ratio of 1.7:1. The ‎prevalence was higher in the 70-84 years old age group (male 33.3-34.8%, female ‎‎19.5-20.8%), while it was relatively low in the 65-69 year old age group and those ‎older adults over 85 years of age. Among the population aged 65 and above, 17.3% men and 9.9% ‎women had frequent urination/ urgency lasting for 1-4 years; 5-9 years in about 4.5% ‎population; 10-19 years in; ‎more than 20 years duration in 1.6% men and 1.9% women. On the severity scale, mild ‎frequent/urgent urination was observed in 24.6% of men and 15.4% women of the ‎Chinese older adults. Moderate cases were observed in 6.3% of men and 2.9% of ‎women, while severe cases were found in 0.8% men and 0.2% women. Benign ‎prostatic hyperplasia (BPH)/ hypertrophy was the main risk factor for frequent/urgent ‎urination in Chinese older adult men (P<0.001). Obesity, hypertension, diabetes, heart ‎disease, anxiety, depression, constipation, and brain injury were the other risk factors for ‎frequent/urgent urination in the Chinese older adult male and female. The results of this ‎survey showed that smoking or drinking habits did not increase the prevalence of ‎frequent/urgent urination in the Chinese older adults.‎